Osseous Reconstruction Using a Membrane Barrier Following Marginal Mandibulectomy: An Animal Pilot Study - Peled, M.; Machtei, E.E.; Rachmiel, A. (Journal of periodontology (1970), 2002)
Background: Invasive and malignant tumors of the oral soft tissues adjacent to the mandible are often treated with partial resection of the osseous structure adjacent to the lesion (marginal mandibulectomy). Autogenous bone graft and composite bone grafts are being used to fill the osseous defects with various degrees of success. The aim of the present study was to explore the utilization of membrane barriers and the principle of guided bone regeneration to negotiate these defects. Methods: Following the removal of P1, P2, and P3, experimental bilateral marginal mandibulectomy defects were created in 4 adult dogs. The bone segments (measuring 25 mm × 15 mm) were then removed. Each side was then randomly selected for either experimental (titanium‐reinforced expanded polytetrafluoroethylene membrane, [ePTFE‐TR]) or control (repositioning flaps) treatment. Postoperatively, the animals were put on soft diet, antibiotics, and analgesics. Sutures were removed under light sedation after 4 weeks, and the area was left to heal and mature for 4 to 6 months (mean 5.3 months). The animals were then sacrificed, and block sections of the mandible were obtained for macroscopic and histological evaluation. Results: The size of the residual defect (the vertical distance between the most apical depression in the ridge and the horizontal line connecting the free gingival margins of the proximal teeth) in the experimental sites (6.10 ± 1.00 mm) was much smaller compared to the controls (10.65 ± 0.82 mm), which was statistically significant (P = 0.0127). Histomorphometric measurements of new bone formation (NBF) revealed a similar pattern: for the experimental sites, NBF was 8.08 ± 0.85 mm compared to 4.99 ± 0.61 mm in the controls. These differences were also statistically significant (P = 0.0257). Conclusions: A regenerative approach to large mandibular osseous defects has been described. If this new treatment modality is further substantiated in other independent studies, it might prove a useful tool in restoring the lost osseous structure associated with marginal mandibulectomy procedures. J Periodontol 2002;73:1451‐1456.